Research on the Permeation Path of Ideological and Political Education in University Brand Color Course - Zhu, Zhijun (Education Insights, 2026)
Entering a new era, higher education faces the critical mission of cultivating modern talents, where "curriculum-based ideological and political education" acts as the core driving force for improving educational quality. Specifically within visual communication and commercial design, university-level brand color coordination courses play an irreplaceable foundational role. These courses extend far beyond teaching physical color mixing or basic aesthetic principles; they profoundly influence the cultural cognition and value orientation of the audience. However, practical teaching observations reveal a common pitfall: current instruction often overemphasizes practical techniques and rapid commercial monetization, severely neglecting the cultivation of humanistic depth and design ethics. To reverse this situation, this paper examines the educational value of brand color coordination courses from the perspective of coordinating aesthetic education with ideological and political education. The study focuses on three key dimensions: exploring the popular "China-fashion" trend to guide students in rediscovering traditional Chinese color aesthetics, thereby fostering deep cultural confidence; employing rigorous standardized training derived from top international brands to meticulously refine college students' craftsmanship spirit; and leveraging the design orientation of green, public welfare brands to encourage calm reflection on consumerist color traps, thereby awakening an inherent sense of social responsibility. A questionnaire survey and teaching tracking of 60 undergraduates validated this approach, revealing significant improvements across all three dimensions. Ultimately, this study demonstrates that integrating ideological concepts into specialized teaching is essential for cultivating young designers with profound expertise and strong moral responsibility.